Keterbatasan Program PHBS dalam Peningkatan Pengelolaan Sampah di RW 5 Kelurahan Ciketing Udik, Kota Bekasi, Jawa Barat - Risca Ardita Novianti; Pudji Muljono; Ekawati Sri Wahyuni (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2021)
Bekasi Municipality as one of DKI Jakarta’s buffer city, has unique challenges in implementing clean and healthy behavior (PHBS). The existence of Bantargebang landfill is one of challanges in optimizing PHBS. The vast amount ofwaste in Bantargebang landfill, including valuable waste, attracts outsiders to engage in waste picking and trading opportunity. This leads to the development of slum areas around the landfill, one of which is in RW 5 Ciketing Udik Subdistrict. This study aims to describe the level of understanding of PHBS and solid waste, waste management and the role of stakeholders in encouraging the improvement of PHBS in waste management. The research design is a qualitative approach with support of quantitative data. Survey showed the community have good understanding about PHBS and adequate understanding about waste management in particular, but respondents also admit they don’t do much to manage their waste. Open burning become as the community preferred way to manage waste. Lack of access to information, enforcement of regulations, and the willingness and ability of community leaders add challenges for developing a good waste management. Furthermore, the implementation of PHBS and the oversight function has not yet reach the overall PHBS indicators, especially waste management.